Illustrated overview and identification key to Cameroonian Ceratocanthinae beetles (Coleoptera: Scarabaeoidea: Hybosoridae) with description of four new species - Ballerio, Alberto; Gill, Bruce D.; Grebennikov, Vasily V. (Zootaxa, 2011)
We summarize present day knowledge on Cameroonian Ceratocanthinae and report new findings made during a monthlong collecting trip in 2006. Four forested localities were surveyed: Mt. Oku at 2200–2800 m, Korup National Park at 300 m, Mt. Kupé at 1550 m and Mt. Cameroon at Bakingili village at 250 m. In total we collected 242 specimens representing 14 species, among them nine species new to Cameroon and eight species likely new to science. Four flightless new species are described: Congomostes hintelmanni n. sp., Baloghianestes oribatidiformis n. sp., B. korupensis n. sp. and B. anceps n. sp. Other Ceratocanthinae species presently known from Cameroon are: Baloghianestes lissoubai Paulian, 1968, Callophilharmostes fleutiauxi (Paulian, 1942), Carinophilharmostes vadoni (Paulian, 1937), Melanophilharmostes burgeoni (Paulian, 1946), M. demirei Paulian, 1977, M. zicsii (Paulian, 1968), Philharmostes (Holophilharmostes) badius (Petrovitz, 1967), Petrovitzostes guineensis (Petrovitz, 1968), P. elytratus (Paulian, 1946), P. endroedyi (Paulian, 1974), along with three unnamed species of Melanophilharmostes Paulian, 1968 and one unnamed species of Pseudopterorthochaetes Paulian, 1977. Twelve Cameroonian Ceratocanthinae species are keyed and all 14 recently collected species are illustrated with habitus images.